Le calcul économique de la publicité frauduleuse - Boyer, Marcel; Kihlstrom, Richard; Laffont, Jean-Jacques (L'Actualité économique)

(untitled) (HEC Montréal, 1979)
The objectif of this paper is to give a microeconomic foundation to misleading advertising in order to derive a method to evaluate its social costs both in terms of efficiency and in terms of distribution. We develop first the approach leading to the concept of demand based on information biased by misleading advertising. Then we set up a model leading to an analytical form of the demand function for the different agents and we discuss the econometric problem of estimating it. We can then develop a formula to measure the social costs of misleading advertising. Finally, we show through an example how that formula can be used.